−6x 2 −2x+5 from 2x^2+82x 2 +8.

Question

−6x
2
−2x+5 from 2x^2+82x
2
+8.

in progress 0
Thiên Ân 1 year 2021-09-04T00:27:27+00:00 1 Answers 3 views 0

Answers ( )

    0
    2021-09-04T00:28:53+00:00

    Answer:

    =90[tex]x^{2}[/tex]+2x+3

    Step-by-step explanation:

    Let’s simplify step-by-step.

    2[tex]x^{2}[/tex] + 82[tex]x^{2}[/tex] + 8 − ( −6[tex]x^{2}[/tex] − 2x + 5 )

    Distribute the Negative Sign:

    = 2[tex]x^{2}[/tex] + 82[tex]x^{2}[/tex] + 8 + − 1 ( − 6[tex]x^{2}[/tex] − 2x + 5 )

    = 2[tex]x^{2}[/tex] + 82[tex]x^{2}[/tex] + 8 + − 1( − 6[tex]x^{2}[/tex] ) + − 1 ( −2x ) + ( − 1 ) ( 5 )

    = 2[tex]x^{2}[/tex] + 82[tex]x^{2}[/tex] + 8 + 6[tex]x^{2}[/tex] + 2x + − 5

    Combine Like Terms:

    = 2[tex]x^{2}[/tex] + 82[tex]x^{2}[/tex] + 8 + 6[tex]x^{2}[/tex] + 2x + −5

    = ( 2[tex]x^{2}[/tex] + 82[tex]x^{2}[/tex] + 6[tex]x^{2}[/tex] ) + ( 2x ) + ( 8 + − 5 )

    = 90[tex]x^{2}[/tex] + 2x + 3

    Hope it helps

    Please mark me as the brainliest

    Thank you

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )